THE NOTION OF EDUCATING FAITH VALUES IN THE NOVEL â€œAPI TAUHIDâ€ BY HABIBURRAHMAN EL SHIRAZY - Suparjo suparjo; Dwi Destiana (Jurnal Penelitian Agama, 2015)
Abstract: Faith or creed education commonly called tauhid is the core of Islamic or tauhid is the soul of life. Along and technology, the development of globalization and ease human social interaction, becomes a kind of obscure threat of moslem faith today. As well as a double-edge knife, the development of technology, can provide benefit and harm. Moral degradation, westemized lifestyle, violence, free sex, and corruption are some other negative impacts. Even more, many radical idiologies with extreme idea. swhich can destroy solidarity for moslem to the other. Those are signs, which show what a bad faith in humanself. In this case, Islamic education has a role with the spirit of "faith" to improve the quality of a moslem's faith. All leaming resources of Islamic education such as religious books, tausiyah, tourism and some Islamic events are the ways which can be used to keep one's faith. Furthermore, novel which can be the medium of faith education will has rule to improve one's faith. The problem statement in this research is to know what are the notion educating faith values in the novel "Api Tauhid" by Habiburrahman El Shirazy. The result of the research which be found in this novel shows that, there are the notion of educating faith values in the novel "Api Tauhid" by Habiburrahman El Shirazy. The main values is faith to Allah SWT (al imanu billah), those are: faith that allah is The One God (tauhid uluhiyah), faith that with the human body, faith the progress of time Allah is The One Creator (Tauhid Rububiyah), faith the atributte of Allah (tauhid asma wa shifat) Keywords: Faith Education, Educating Faith Values, "Api Tauhid" Novel.